Metastable Iron Sulfides Gram‐Dependently Counteract Resistant Gardnerella Vaginalis for Bacterial Vaginosis Treatment. Issue 10 (5th February 2022) - Fang, Ling; Ma, Ruonan; Gao, Xuejiao J.; Chen, Lei; Liu, Yuan; Huo, Yanwu; Wei, Taotao; Wang, Xiaonan; Wang, Qian; Wang, Haojue; Cui, Chengjun; Shi, Qifeng; et al.
Abstract: Bacterial vaginosis (BV) is the most common vaginal infection found in women in the world. Due to increasing drug‐resistance of virulent pathogen such as Gardnerella vaginalis ( G. vaginalis ), more than half of BV patients suffer recurrence after antibotics treatment. Here, metastable iron sulfides (mFeS) act in a Gram‐dependent manner to kill bacteria, with the ability to counteract resistant G. vaginalis for BV treatment. With screening of iron sulfide minerals, metastable Fe3 S4 shows suppressive effect on bacterial growth with an order: Gram‐variable G. vaginalis >Gram‐negative bacteria>> Gram‐positive bacteria. Further studies on mechanism of action (MoA) discover that the polysulfide species released from Fe3 S4 selectively permeate bacteria with thin wall and subsequently interrupt energy metabolism by inhibiting glucokinase in glycolysis, and is further synergized by simultaneously released ferrous iron that induces bactericidal damage. Such multiple MoAs enable Fe3 S4 to counteract G. vaginalis strains with metronidazole‐resistance and persisters in biofilm or intracellular vacuole, without developing new drug resistance and killing probiotic bacteria. The Fe3 S4 regimens successfully ameliorate BV with resistant G. vaginalis in mouse models and eliminate pathogens from patients suffering BV. Collectively, mFeS represent an antibacterial alternative with distinct MoA able to treat challenged BV and improve women health. Abstract : Metastable iron sulfides (mFeS) demonstrate a Gram‐dependent antibacterial activity by releasing polysulfide species that penetrate bacteria with thin wall. The polysulfides then disrupt glycolytic energy metabolism and synergize with iron to kill bacteria without inducing new drug resistance. These mechanisms of action enable mFeS to counteract metronidazole‐resistant Gardnerella vaginalis, biofilm, and intracellular persister in bacterial vaginosis treatment.